Exploring the Frontiers of Cell Temperature Measurement and Thermogenesis - Zhu, Hanliang; Xu, Haotian; Zhang, Yue; Brodský, Jan; Gablech, Imrich; Korabečná, Marie; Neuzil, Pavel (Advanced science, 2025)
The precise measurement of cell temperature and an in-depth understanding of thermogenic processes are critical in unraveling the complexities of cellular metabolism and its implications for health and disease. This review focuses on the mechanisms of local temperature generation within cells and the array of methods developed for accurate temperature assessment. The contact and noncontact techniques are introduced, including infrared thermography, fluorescence thermometry, and other innovative approaches to localized temperature measurement. The role of thermogenesis in cellular metabolism, highlighting the integral function of temperature regulation in cellular processes, environmental adaptation, and the implications of thermogenic dysregulation in diseases such as metabolic disorders and cancer are further discussed. The challenges and limitations in this field are critically analyzed while technological advancements and future directions are proposed to overcome these barriers. This review aims to provide a consolidated resource for current methodologies, stimulate discussion on the limitations and challenges, and inspire future innovations in the study of cellular thermodynamics.
Keywords: Temperature; teplota; termometrie; Thermogenesis; Animals; lidé; Thermometry; termogeneze; Humans; Thermography; termografie; zvířata